The State of Knowledge of Outdoor Orientation Programs: Current Practices, Research, and Theory. (March 2014) - Bell, Brent J.; Gass, Michael A.; Nafziger, Christopher S.; Starbuck, J. David
Outdoor orientation programs represent a prominent area of experiential education with over 25, 000 participants annually. More than 191 outdoor orientation programs currently operate in the United States and Canada. The research examining outdoor orientation programs consists of 25 peer-reviewed published studies and 11 dissertations. A new theory explaining the success of these programs has emerged based on research and the belief that students experience a special sense of belongingness promoted by social dynamics found in these programs.